(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: Thyroid nodules are seen in 4-7% of the population which are more common in women. Excising all of these lesions is impractical and associated with certain risk factors as well. Fine needle aspiration (FNA) biopsy is the most relevant diagnostic procedure to decide those that need to be surgically excised or not. Methodology: The present study was conducted in Liban clinic, Mogadishu, Somalia. 220 patients whom were diagnosed with various types of tyroid lesions within 2 years of period were included in the study. Main objectives were to put forward the distribution of histological findings according to fine needle aspiration (FNA) biopsy results among different age groups, and to define the prevelance of certain subtypes of thyroid nodules in the region. Results: 207 patients had ‘benign’ nodules and 13 patients had ‘malignant’ nodules according histological evaluationof fine needle aspiration (FNA) biopsy results. ‘31-40’ years of age interval was found to have the highest percentage of histologically ‘benign findings’, while patients within ‘41-50’ years of age had the highest rate of ‘malignant lesions’ in count among the study population. ‘Papillary’ (n=8)(61.5%) and ‘medullary’ (n=5)(38.5%) carcinomas were most common malignant features.Mostly recorded benign lesions were ‘colloidal goiter, multinodular goiter (MNG), nodular hyperplasia and adenomatoid goiter’ (n=94)(45.4%). Conclusion: Characteristics of thyroidlesions in region of Mogadishu, Somalia show similar patterns based upon correlation of age with histological differences compared to recent literature. With the aid of FNA, majority of the population can be managed conservatively safely without need of surgical interventions. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 67-71